SLC4A11 Revisited: Isoforms, Expression, Functions, and Unresolved Questions - Polina Alekseevna Kovaleva; Elena Sergeevna Kotova; Elena Ivanovna Sharova; Liubov Olegovna Skorodumova (Biomolecules)
The SLC4A11 gene encodes a membrane transporter implicated in congenital hereditary endothelial dystrophy, Harboyan syndrome, and certain cancers. Despite its clinical importance, current data on SLC4A11 expression patterns, transcript variants, and functional roles remain inconsistent and sometimes contradictory. We have systematized existing data, identified areas of consensus, and highlighted discrepancies. This review addresses SLC4A11 transcript and isoform diversity and how this complexity influences both the interpretation of its tissue expression patterns (particularly in the corneal endothelium) and the investigation of its functional roles in health and disease. Our review also untangles the evolving understanding of SLC4A11 function, from its initial classification as a bicarbonate transporter to its established roles in NH3- and pH-regulated H+/OH− transport, lactate efflux, cellular stress responses, and adhesion. The review details how pathogenic mutations disrupt protein maturation, membrane localization, or transport activity, contributing to corneal fluid imbalance and disease. We also discuss the emerging role of SLC4A11 in cancer metabolism and the common metabolic features of dystrophic corneas and tumors. Methodological challenges are appraised, encouraging caution in interpretation and the need for isoform-specific studies. Overall, this review provides a comprehensive update on SLC4A11 biology and identifies key gaps for future research.